Discovery of novel PARP1/NRP1 dual-targeting inhibitors with strong antitumor potency - Liu, Juanjuan; Geng, Yifei; Jiang, Su; Guan, Lixia; Gao, Junyi; Niu, Miao-Miao; Li, Jindong (Frontiers in Pharmacology, 2024)
Given that overexpression of Poly (ADP-ribose) polymerase-1 (PARP1) and Neuropilin-1 (NRP1) is implicated in the pathogenesis of human breast cancer, the design of dual PARP1/NRP1 inhibitors has wide therapeutic prospect. However, there have been no reports of such inhibitors so far. Herein, we discovered novel small molecule inhibitors that simultaneously target PARP1 and NRP1 using structure-based virtual screening for the treatment of breast cancer. Notably, PPNR-4 was the most potent inhibitor targeting PARP1 (IC50 = 7.71 ± 0.39 nM) and NRP1 (IC50 = 24.48 ± 2.16 nM). PPNR-4 showed high affinity and binding stability to PARP1 and NRP1. The cytotoxicity assays showed that PPNR-4 demonstrated significant antiproliferative activity on MDA-MB-231 cells (IC50 = 0.21 μM) without effect on normal human cells. In vivo experiments exhibited that PPNR-4 showed more effective than the positive controls in inhibiting the growth of tumors. Overall, these data suggest that PPNR-4 is an effective antitumor candidate and deserves further research.